Cross-cultural training in female expatriation and repatriation : Experiences of seven Finnish female managers - Kim, Maria (My University, 2018)
Expatriation and international assignments have always been a popular subject in research of international business. Repatriation, on the other hand, has not been that widely studied. Both phenomena have been mainly investigated from the comprehensive view not dividing male and female expatriates. It is known that the number of female managers sent out to complete international assignments is fairly small compared to the number of male managers. Despite the small number of female expatriates, their proportion has grown over the years (1999−2016) from 2% to 25%. Thus, justifying that this subject should be researched more. In addition to this, the expatriation and repatriation have been studied as separate components not viewing them as two parts of one and the same process. The objective of this study is to understand how cross-cultural training can enhance cross-cultural adjustment of female managers in expatriation and repatriation. Thus, linking both expatriation and repatriation to represent one whole process. This research was conducted through multiple case study, and data was collected with semi-structured interviews. In total, seven female managers from different business fields were interviewed throughout autumn 2018 to understand the phenomenon. The interviews were transcribed and categorised in themes to have an in-deep understanding of the subject. The results show that the interviewees believe cross-cultural training prior international assignment to be important and prepare the upcoming expatriates to what is coming when they relocate. Additionally, the findings indicate that the interviewees believe that the best way to have the most benefit from cross-cultural training is for it to be tailor-made in accordance to the cross-cultural background, skills and experience of the upcoming expatriate. In regards to the repatriation training and repatriation process, on the other hand, the results show that most of the repatriates do not feel they need repatriation training as it is the responsibility of the returning individual to be up-to-date in organisational changes as well as in their personal life. However, some of the interviewees stated that if the returning employee does not have that much of experience in living abroad and returning home, the repatriation training in this case is beneficial for this person and should cover stress management and coping techniques. Based on the findings of this research, it is important for organisations to create an open and encouraging atmosphere for their employees to not be afraid for applying for international assignments. Thus, widening their candidate pool and finding the most appropriate people for expatriate assignments. Additionally, the findings support previous empirical evidence that cross-cultural training smoothens the cross-cultural adjustment of the expatriates when they relocate to an unfamiliar country.
Keywords: Cross-cultural training, cross-cultural adjustment, expatriation, repatriation, expatriates, repatriates, female managers